Psychological Impact on Stunting Adolescents: Literature Review Study - Delima, Delima; Neviyarni, Neviyarni; Marjohan, Marjohan; Ifdil, Ifdil; Afdal, Afdal (REAL in Nursing Journal, 2023)
Background: The impact caused by stunting is not only on physical development but will also have an impact on the child's psychology. Adolescents with stunting need to have high spirits so that they can be able and survive in life they avoid psychological impacts such as stress, withdrawal, depression, anxiety, and fear. The purpose of this study was to see the psychological impact caused by stunting in adolescence. Methods: The literature review method was used to search for articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline. Results: The search was carried out using the keywords "stunting", "psychological impact", "adolescents", "anxiety", and "stress". Analysis conducted by the authors of 6 relevant articles found that there was a psychological impact on adolescents with stunting. Conclusion: The existence of counseling teachers can provide information services to develop positive potential in students, besides that social support and efficient parenting are needed so that teenagers can overcome the psychological impact they experience so that they can get through adolescence and plan for the well future.Keywords: Stunting; Psychological Impact; Adolescents